High‐Dose Human Milk Feedings Decrease Oxidative Stress in Premature Infant. Issue 1 (15th May 2018) - Chen, Yimin; Fantuzzi, Giamila; Schoeny, Michael; Meier, Paula; Patel, Aloka L.
Abstract: Background: Premature infants are susceptible to oxidative stress, increasing the risk for serious morbidities. High‐dose human milk (HM) feedings decrease morbidity risks and may reduce oxidative stress in this population. The purpose of this study was to compare oxidative stress using serial urinary F2 ‐isoprostane concentrations in predominantly HM and preterm formula (PF)–fed premature infants over the first 21 days of life (DOL), while controlling for perinatal oxidative stress exposures including bovine‐based human milk fortifier (HMF) or PF introduction to predominantly HM‐fed infants. Methods: This was a quasi‐experimental design that categorized 22 premature infants into mutually exclusive comparison groups based on exposure to HM and PF. Serial urine samples (before and after first feeding, and DOL 7, 14, and 21) were used to determine urine F2 ‐isoprostane concentrations measured by enzyme‐linked immunosorbent assays. We analyzed data using Mann‐Whitney U test, Wilcoxon rank test, and multilevel models. Results: Comparing the predominantly HM‐fed and predominantly PF‐fed groups over time, median F2 ‐isoprostane concentrations decreased significantly in the predominantly HM group ( P = .003) and increased significantly in the predominantly PF group ( P = .01). Perinatal oxidant exposures and the introduction of HMF did not affect results. Conclusions: Our results demonstrate that predominantly HM feedings were associated with decreased oxidative stress, whereas PF feedings increased oxidative stress in premature infants, even after controlling for perinatal oxidant exposures of HMF or PF introduction.